KAJIAN PUSTAKA: PEMANFAATAN PODCAST SPOTIFY DALAM PEMBELAJARAN LISTENING MAHASISWA EFL - Aliya Zulva Ahsani; Dhamar Ibrahim Kadista Putra; Wiwin Luqna Hunaida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mobile-Assisted Language Learning (MALL) is currently taking over the teaching of English as a Foreign Language (EFL), with Spotify being a popular tool for improving listening comprehension. However, it ignores the possibility of cognitive overload and the appearance of productivity, and it is erroneous to assume that autonomous technology adoption invariably enhances understanding. The purpose of this study is to investigate the patterns, advantages, difficulties, and efficacy of utilizing Spotify podcasts in EFL listening comprehension. Data were gathered using a literature review process from a variety of scientific publications that had been published in the previous ten years via indexed academic sources. There are four major conclusions from the analysis. First, because of the platform's entertainment algorithms, the trend of autonomy frequently results in passive listening, which calls for metacognitive techniques. Third, there is a chance of mistake fossilization and cognitive overload due to the absence of visual signals and immediate feedback. Fourth, more time spent on the assignment and the use of pedagogical scaffolding are more important for improving scores than the application alone. In summary, Spotify is an essential source of language input, but rather than operating as a stand-alone learning environment, its overall efficacy is entirely dependent on the combination of instructors' instructional design and students' metacognitive discipline.